Contrasting patterns of phylogenetic diversity and alpine specialization across the alpine flora of the American mountain range system - Figueroa, Hector Fox; Marx, Hannah E.; de Souza Cortez, Maria Beatriz; Grady, Charles J.; Engle-Wrye, Nicholas; Beach, Jim; Stewart, Aimee; Folk, Ryan A.; Soltis, Douglas E.; Soltis, Pamela S.; Smith, Stephen A. (Zenodo, 2021)
Although mountainous habitats contribute substantially to global biodiversity, comparatively little is known about biogeographic patterns of distributions of alpine species across multiple mountain ranges. Here, we present a detailed analysis of the distributions and phylogenetic affinities of alpine seed plant lineages across North, Central, and South American mountain systems. Using a comprehensive dataset that characterized the elevational niches of American seed plants in a continuously valued way, we were able to quantitatively investigate how the proportion of alpine habitat occupied by plants related to their biogeographic distributions at a regional scale and place these results in a phylogenetic context. We found alpine species diversity to be greatest in the central Andes and western North America, and that sites with lower phylogenetic diversity contained species with a greater degree of alpine specialization. In particular, near Arctic/ boreal alpine communities were characterized by low phylogenetic diversity and higher degrees of alpine specialization, whereas the opposite was observed for southern Patagonian communities. These results suggest that abiotic filtering alone in these climatically similar regions is unlikely to explain alpine community assembly. Nevertheless, the overall relative rarity of alpine specialists, and the tendency for such specialists to be most closely related to montane lineages, suggested that filtering was still an important factor in shaping alpine community structure. This work corroborates the importance of a nuanced and scale-dependent perspective on the 'history-filtering' debate axis, as both factors have likely contributed to modern biodiversity patterns observed in alpine plant communities across the Americas. File Descriptions: "alpine_taxonomy_v9.csv" This CSV file lists all 2397 alpine species in our dataset. "strategy" column indicates if this species was classified as Alpine Specialist (AS), or Alpine Generalist (AG), with subcategories of primarily ...